Pemberdayaan Masyarakat Dalam Meningkatkan Lingkungan Desa Ulumahuam yang Lebih Unggul - Ayu Intan Pratiwi; Alwi Pranata Rambe; Indah Wahyuni; Muliani Putri; Syahdinar Nasution (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine empowerment through formal and non-formal education in carrying out training activities for the Ulumahuam Village community to improve the superior environment of Ulumahuam Village in South Labuhanbatu Regency. The research method is a qualitative research conducted by collecting data, observation methods, documentation, and interviews with the Ulumahuam Village apparatus and the Ulumahuam Village community and the Ulumahuam Village Community Leaders, South Labuhanbatu Regency. The results of the study, namely (1) the community empowerment process to improve the superior environment of Ulumahuam Village (2) the empowerment process carried out by formal and non-formal educational institutions has not met the expectations of the learning citizens involved in the process, and has not paid attention to aspects of the needs needed by the learning community. , (3) the results generated after participating in the empowerment process in formal and non-formal educational institutions have not helped the community to improve their lives, (4) the cooperative relationship that has been built by LPM and Ulumahuam Village to make Ulumahuam Village superior Keywords: CommunityEmpowerment, Improving the Environment, Ulumahuam Village, More Superior